2010
DOI: 10.1021/es100382z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Perfluorinated Compounds in the Upper Mississippi River Basin

Abstract: Despite ongoing efforts to develop robust analytical methods for the determination of perfluorinated compounds (PFCs) such as perfluorooctanesulfonate (PFOS) and perfluorooctanoic acid (PFOA) in surface water, comparatively little has been published on method performance, and the environmental distribution of these materials remains poorly described worldwide. In this study, an existing method was improved and applied in a large-scale evaluation of the Upper Mississippi River Basin, one of the largest watershe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 17 publications
2
63
1
Order By: Relevance
“…Some previous studies have also reported the occurrence of PFASs, especially PFOA and PFOS in river water globally (Hansen et al, 2002;Mclachlan et al, 2007;Murakami et al, 2008;Yeung et al, 2009;Nakayama et al, 2010;Hong et al, 2013;Wang et al, 2013;Zhang et al, 2013). In general, the PFAS concentrations in the Yangtze River were lower than those in other rivers in the world.…”
Section: Concentrations and Composition Of Pfass In Surface Watermentioning
confidence: 84%
See 1 more Smart Citation
“…Some previous studies have also reported the occurrence of PFASs, especially PFOA and PFOS in river water globally (Hansen et al, 2002;Mclachlan et al, 2007;Murakami et al, 2008;Yeung et al, 2009;Nakayama et al, 2010;Hong et al, 2013;Wang et al, 2013;Zhang et al, 2013). In general, the PFAS concentrations in the Yangtze River were lower than those in other rivers in the world.…”
Section: Concentrations and Composition Of Pfass In Surface Watermentioning
confidence: 84%
“…the PFOA and PFOS concentrations in Tamagawa were 107 ng/L and 143 ng/L; tens to hundreds of ng/L for individual PFAS in Mississippi river) (Yeung et al, 2009;Nakayama et al, 2010), the mass loading of PFASs in the Yangtze River are still higher than those in other rivers due to its huge annual water flow (annual mass loading of PFOA and PFOA in Tamagawa were 0.045 tons and 0.060 tons) (Yeung et al, 2009). But the mass loading of PFASs was slightly lower than the European rivers, with the annual mass loading of PFHxA, PFHpA, PFOA and PFNA being 2.8 tons, 0.86 tons, 14.3 tons and 0.26 tons (McLachlan et al, 2007), and much lower than that in the Mississippi River with higher PFAS concentrations (Nakayama et al, 2010). Considering their persistence and bioaccumulation properties, the PFASs in the Yangtze River would be transported to the East China Sea, and finally into the ocean.…”
Section: Estimated Annual Mass Loadings Of Pfass In the Yangtze Rivermentioning
confidence: 99%
“…S1), has been identified as an emerging contaminant of global concern (Nakayama et al, 2010;Zhang et al, 2013). Worldwide distribution and contamination of PFOS pose great threat not only to the environment, but also to the animal and human health (Beach et al, 2006;Betts, 2008;Nelson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Each is run by its own local council, which has its headquarters in the principal town. The 10 PFCs were selected according to their occurrence in water as reported in other publications (Mak et al 2009;Nakayama et al 2010;Skutlarek et al 2006). Additional goals were to observe the distribution of the composition profile in groundwater and surface-water samples and to evaluate the potential PFC exposure of a significant part of the French population due to water consumption.…”
mentioning
confidence: 99%